High capacity binder-free nanocrystalline GeO2 inverse opal anodes for Li-ion batteries with long cycle life and stable cell voltage. (January 2018) - McNulty, David; Geaney, Hugh; Buckley, Darragh; O'Dwyer, Colm
Abstract: We demonstrate that crystalline macroporous GeO2 inverse opals exhibit state-of-the-art capacity retention, voltage stability and a very long cycle life when tested as anode materials for Li-ion batteries. The specific capacities and capacity retention obtained from GeO2 IOs are greater than values reported for other GeO2 nanostructures and comparable to pure Ge nanostructures. Unlike pure Ge nanostructures, GeO2 IOs can be prepared in air without complex processing procedures, potentially making them far more attractive from an industrial point of view, in terms of cost and ease of production. Inverse opals are structurally and electrically interconnected, and remove the need for additives and binders. GeO2 IOs show gradual capacity fading over 250 and 1000 cycles, when cycled at specific currents of 150 and 300 mA/g, respectively, while maintaining high capacities and a stable overall cell voltage. The specific capacities after the 500th and 1000th cycles at a specific current of 300 mA/g were ~ 632 and 521 mA h/g respectively, corresponding to a capacity retention in each case of ~ 76% and 63% from the 2nd cycle. Systematic analysis of differential capacity plots obtained from galvanostatic voltage profiles over 1000 cycles offers a detailed insight into the mechanism of charge storage in GeO2 anodes over their long cycle life. Rate capability testing and asymmetric galvanostatic testing demonstrate the ability of GeO2 IO samples to deliver significantly high capacities even at high specific currents (1 A/g). Graphical abstract: Highlights: Crystalline macroporous GeO2 inverse opals exhibit state-of-the-art capacity retention, voltage stability and a very long cycle life. The anode uses structured porosity to remove the need for conductive additives or binders to form a slurry or electrode casting. Detailed insight in to the mechanism of reversibly lithiation of Ge from interconnected GeO2 nanocrystals. Exceptional voltage stability and rate performance, with high capacity up to 1 A/g rates. Relatively low temperature route to Ge-based nanomaterials for high capacity Li-ion battery anodes.